Therapies in preclinical and clinical development for Angelman syndrome. (3rd July 2021) - Markati, Theodora; Duis, Jessica; Servais, Laurent
ABSTRACT: Introduction : Angelman syndrome is a rare genetic neurodevelopmental disorder, caused by deficiency or abnormal function of the maternal ubiquitin protein-ligase E3A, known as UBE3A, in the central nervous system. There is no disease-modifying treatment available, but the therapeutic pipeline of Angelman syndrome includes at least 15 different approaches at preclinical or clinical development. In the coming years, several clinical trials will be enrolling patients, which prompted this comprehensive review. Areas covered : We summarize and critically review the different therapeutic approaches. Some approaches attempt to restore the missing or nonfunctional UBE3A protein in the neurons via gene replacement or enzyme replacement therapies. Other therapies aim to induce expression of the normal paternal copy of the UBE3A gene by targeting a long non-coding RNA, the UBE3A-ATS, which interferes with its own expression. Another therapeutic category includes compounds that target molecular pathways and effector proteins known to be involved in Angelman syndrome pathophysiology. Expert opinion : We believe that by 2022–2023, more than five disease-modifying treatments will be simultaneously at clinical testing. However, the are several challenges with regards to safety and efficacy, which need to be addressed. Additionally, there is still a significant unmet need for clinical trial readiness.